Lumasaaba and English Language Reading Comprehension among Primary School Pupils of Sironko District in Uganda - Namukuta, Zainorice; Buyera, Geofrey (East African Nature and Science Organization, 2024)
The study investigated the effect of Lumasaaba on English language Reading Comprehension among Primary School Pupils in the Sironko district. Two objectives guided the study: to find out the effect of Lumasaaba orthographic patterns and Lumasaaba Cognate awareness on English Language reading comprehension. Much as several studies showed that Lumasaaba and the English language share some linguistic features like the alphabet and cognates, there was a dearth of studies that identify which features of Lumasaaba need to be shared for transfer to be effective and to demonstrate whether pupils were aware of these cognates, and activate them in reading comprehension. The study used a cross-sectional survey research design to assess the effect of Lumasaaba on pupils’ English reading comprehension in Mafudu Sub County, Budadiri West, Sironko District in Uganda. The study used a language test to evaluate Primary Five (P5) pupils’ English reading comprehension, cognate awareness, and spelling proficiencies. The results showed that pupils who did not receive Lumasaaba instruction performed slightly better than those pupils who received Lumasaaba instruction. Besides, Lumasaaba orthography and cognates were significant predictors of English language reading comprehension proficiency, Lumasaaba Cognates emerged as the most significant predictor (β = .294, p= .000 compared to Lumasaaba Orthography (β = .196, p= .006). The researchers conclude that lexical similarities between Lumasaaba and English as well as the nature of Lumasaaba writing patterns enhance English language reading comprehension proficiency. The findings highlight the need for educators to consider Lumasaaba orthographic patterns and cognates when designing reading instruction for Lumasaaba bilingual pupils